1997
DOI: 10.1180/claymin.1997.032.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aminotriazole with montmorillonite and Mg-vermiculite at pH 4

Abstract: The interaction of aminotriazole (AMT) at pH 4 on Wyoming montmorillonite (mainly with Na ions) and Mg-vermiculite has been studied by X-ray diffraction and infrared spectroscopy. The AMT is adsorbed on montmorillonite in the cationic form by cation exchange. The amount of pesticide adsorbed was 71 mEq/100 g, which comprises ~91% of the CEC of this sample (78.2 mEq/100 g). Saturation was reached in 24 h, giving rise to a complex with basal spacing 12.5 ,~. Vermiculite adsorbs 167 mEq/100 g,o almost 20% greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the case of compounds having CN bonds such as acrylonitrile, it is reported that a dipole moment exists between CN groups and interlayer ions (Yamanaka et al, 1974(Yamanaka et al, , 1975. In the case of some organic compounds such as aminotriazole, it is suggested that not only is adsorption caused by dipole moments but also adsorption can be due to interactions between amino groups and interlayer ions of Mont and the resultant formation of complexes (Morillo et al, 1997;Serratosa, 1968). The sum of these studies show that not only interactions with the clay structure but also interactions with interlayer ions has an influence on the adsorption characteristics of organic compounds onto Mont and that there is a possibility that control of adsorption characteristics can be achieved by controlling the interlayer ions.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of compounds having CN bonds such as acrylonitrile, it is reported that a dipole moment exists between CN groups and interlayer ions (Yamanaka et al, 1974(Yamanaka et al, , 1975. In the case of some organic compounds such as aminotriazole, it is suggested that not only is adsorption caused by dipole moments but also adsorption can be due to interactions between amino groups and interlayer ions of Mont and the resultant formation of complexes (Morillo et al, 1997;Serratosa, 1968). The sum of these studies show that not only interactions with the clay structure but also interactions with interlayer ions has an influence on the adsorption characteristics of organic compounds onto Mont and that there is a possibility that control of adsorption characteristics can be achieved by controlling the interlayer ions.…”
Section: Introductionmentioning
confidence: 99%